2020
DOI: 10.33314/jnhrc.v18i3.2584
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Attitude Regarding Cervical Cancer Screening among Reproductive Age Women

Abstract: Background: Cervical cancer is preventable so awareness can be as effective as any other method to prevent it.The study aims to assess awareness and attitude regarding cervical cancer screening among reproductive age women in a tertiary level hospital, Kathmandu, Nepal. Methods: A descriptive cross sectional study was carried out among 170 reproductive age women attending Nepal Medical College Teaching Hospital using purposive sampling technique. A semi structured interview schedule was used to collect d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…All studies were published between 2001 and 2021, and nearly half (45%) within the last 5 years. Twenty-seven (71%) studies focused on CC (Baral et al 2020;Bhatta et al 2020;Darj et al 2019;Ghimire and Pathak 2020;Andersen et al 2020;Gyenwali et al 2013;Johnson et al 2014;Joy et al 2011;Khadka et al 2017;Maharjan et al 2020;Pandey and Karmacharya 2017;Poudel and Sumi 2019;Rachana and Giri 2019;Ranabhat et al 2014;Ranjit et al 2016;Satyal 2013;Shakya et al 2016;Sherpa 2007;Sherpa et al 2020;Shrestha et al 2013;Shrestha 2014;Shrestha and Dhakal 2017;Shrestha et al 2020;Shrestha et al 2021a;Thapa 2018;Thapa et al 2018;). Ten studies (26%) concerned BC (Bhandari et al 2016;Bhandari et al 2021;Bhatt et al 2011;Braun and Itano 2011;Gupta et al 2015;Narasingrao et al 2013;Parajuli and Mandal 2010;Sathian et al 2014;Shrestha 2012;).…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies were published between 2001 and 2021, and nearly half (45%) within the last 5 years. Twenty-seven (71%) studies focused on CC (Baral et al 2020;Bhatta et al 2020;Darj et al 2019;Ghimire and Pathak 2020;Andersen et al 2020;Gyenwali et al 2013;Johnson et al 2014;Joy et al 2011;Khadka et al 2017;Maharjan et al 2020;Pandey and Karmacharya 2017;Poudel and Sumi 2019;Rachana and Giri 2019;Ranabhat et al 2014;Ranjit et al 2016;Satyal 2013;Shakya et al 2016;Sherpa 2007;Sherpa et al 2020;Shrestha et al 2013;Shrestha 2014;Shrestha and Dhakal 2017;Shrestha et al 2020;Shrestha et al 2021a;Thapa 2018;Thapa et al 2018;). Ten studies (26%) concerned BC (Bhandari et al 2016;Bhandari et al 2021;Bhatt et al 2011;Braun and Itano 2011;Gupta et al 2015;Narasingrao et al 2013;Parajuli and Mandal 2010;Sathian et al 2014;Shrestha 2012;).…”
Section: Search Resultsmentioning
confidence: 99%
“…The majority of studies used researcher-or clinician-administered (semi-)structured surveys (n = 25, 66%) in face-to-face interviews, or self-administered surveys (n = 8, 21%). Ten studies reported knowledge or awareness scores, predominantly focusing on CC (Bhatt et al 2011;Baral et al 2020;Darj et al 2019;Ghimire and Pathak 2020;Khadka et al 2017;Poudel and Sumi 2019;Rachana and Giri 2019;Shrestha et al 2013;Shah et al 2010;Shrestha and Dhakal 2017). A review of medical records was carried out in one study (Shrestha 2014), and two studies offered women a Papanicolaou or Pap smear test (Ranabhat et al 2014;Sherpa 2007).…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations